Renting versus owning and the role of income risk: The case of Germany - Rainer Schulz; Martin Wersing; Axel Werwatz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
In a world with complete markets and no transactions cost, the decision whether to rent or buy a home is separate from a household's professional income risk. If markets are incomplete and have frictions, however, profession- specific income risk, regional house price risk, and mobility needs will interact and should affect the tenure mode choice. Using panel data from West Germany, we establish homogeneous profession groups and estimate their regional net income risk and regional mobility. We then examine the impact of the risk and mobility variables on the tenure mode decision at the aggregate and the individual household level. We find that the diversification potential of renting affects the tenure mode choice as do mobility needs.
Keywords: R21; G11; J24; C25; 330; Tenure mode choice; background risk; household mobility; Besitzformwahl; Wohnungswechsel; Haushaltseinkommen; Risiko; Binnenwanderung; Schätzung; Deutschland